Role of Innate Immunity in Neonatal Infection - Cuenca, Alex G.; Wynn, James L.; Moldawer, Lyle L.; Levy, Ofer (American Journal of Perinatology, 2013)
Newborns are at increased risk of infection due to genetic, epigenetic, and environmental factors. Herein we examine the roles of the neonatal innate immune system in host defense against bacterial and viral infections. Full-term newborns express a distinct innate immune system biased toward TH2-/TH17-polarizing and anti-inflammatory cytokine production with relative impairment in TH1-polarizing cytokine production that leaves them particularly vulnerable to infection with intracellular pathogens. In addition to these distinct features, preterm newborns also have fragile skin, impaired TH17-polarizing cytokine production, and deficient expression of complement and of antimicrobial proteins and peptides (APPs) that likely contribute to susceptibility to pyogenic bacteria. Ongoing research is identifying APPs, including bacterial/permeability-increasing protein and lactoferrin, as well as pattern recognition receptor agonists that may serve to enhance protective newborn and infant immune responses as stand-alone immune response modifiers or vaccine adjuvants.
Keywords: adjuvants; neonatal sepsis; pathogen recognition receptors; innate immunity